A major change in precipitation gradient on the Chinese Loess Plateau at the Pliocene-Quaternary boundary. (15th April 2018) - Peng, Wenbin; Nie, Junsheng; Wang, Zhao; Qiang, Xiaoke; Garzanti, Eduardo; Pfaff, Katharina; Song, Yougui; Stevens, Thomas
Graphical abstract: Highlights: New application of heavy mineral analysis as a long-term paleoclimate indicator. Precipitation gradient on the CLP changed at the Pliocene-Quaternary boundary. Decreased meridional moisture transport caused the changes in climatic gradients. Abstract: Spatiotemporal variations in East Asian Monsoon (EAM) precipitation during the Quaternary have been intensively studied. However, spatial variations in pre-Quaternary EAM precipitation remain largely uninvestigated, preventing a clear understanding of monsoon dynamics during a warmer climatic period. Here we compare the spatial differences in heavy mineral assemblages between Quaternary loess and pre-Quaternary Red Clay on the Chinese Loess Plateau (CLP) to analyze spatial patterns in weathering. Prior studies have revealed that unstable hornblende is the dominant (∼50%) heavy mineral in Chinese loess deposited over the past 500 ka, whereas hornblende content decreases to <10% in strata older than ∼1 Ma in the central CLP because of diagenesis. In the present study we found that hornblende is the dominant heavy mineral in 2–2.7 Ma loess on the northeastern CLP (at Jiaxian), which today receives little precipitation. Conversely, hornblende content in the upper Miocene-Pliocene Red Clay at Jiaxian is <10%, as in the central CLP. The early Quaternary abundance of hornblende at Jiaxian indicates that the current northwestward-decreasing precipitation pattern and consequent dry climate at Jiaxian must have been initiated since ∼2.7 Ma, preventing hornblende dissolution to amounts <10% as observed in the central CLP. By contrast, the 7 Ma and 3 Ma Jiaxian Red Clay hornblende content is significantly less than that of the Xifeng samples, despite the fact that today Xifeng receives more precipitation than Jiaxian, with expected enhanced hornblende weathering. This suggests that the northeastern CLP received more precipitation during the Late Miocene-Pliocene than at Xifeng, indicating that the precipitation gradient on the CLP was more east–west during the Late Miocene-Pliocene rather than northwest-southeast as it was in the Quaternary. A comparison of magnetic susceptibility records for these sections confirms this inference. We attribute this major change in climatic patterns at ∼2.7 Ma to decreased northward moisture transportation associated with Northern Hemisphere glaciation and cooling in the Quaternary. This study therefore demonstrates the potential usefulness of employing heavy mineral analysis in both paleoclimatic and paleooceanographic reconstructions.